Existence and boundary asymptotic behavior of large solutions of Hessian equations. (October 2019) - Ma, Shanshan; Li, Dongsheng
Abstract: In this paper, we establish the existence of large solutions of Hessian equations and obtain a new boundary asymptotic behavior of solutions.